The relation between meal frequency and obesity in adults - Muftuoglu, Selen; Ozdemir, Merve; Saka, Mendane; Akçil Ok, Mehtap; Koseler, Esra; Bayram, Sinem; Yesil, Esen; Kose, Beril; Turker, Perim; Ercan, Aydan; Aksoydan, Emine; Tayfur, Muhittin; et al. (Progress in Nutrition, 2018)
Objective: To determine the relation between meal frequency and obesity in adults. Methods: A cross-sectional study was done among 1829 volunteer (520 men, 1309 women) selected through a multi-stage stratified random sampling method during 2015/2016. A standardized, confidential data collection sheet was used. It included socio-demographic factors, dietary behaviors, anthropometric measurements and energy-macro and micronutrient intakes. Results: The median meal frequency of women and men were 4 and 3, respectively. Approximately 57% of men and 61% of women have skipped meals and 76.8% of them were skipped their lunch. In addition, the individuals whose BMI were under and over 25 kg/m2 (72.4%, 78.3%, respectively) often skipped lunch. The meal frequency positively correlated with waist to hip ratio in women (p